The use of team pair solo technique combined with picture as medium in teaching writing descriptive text - Muamalah, Siti (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
This study was conducted to explore the implementation of Team Pair Solo and picture by an English teacher in teaching writing descriptive text. The aim was to describe the implementation of Team Pair Solo and picture in teaching writing descriptive text by English teacher, reveal the difficulties that faced by English teacher in teaching writing descriptive text using Team Pair Solo and picture, and explain how the English teacher solves those difficulties. In this study, I used qualitative method. The participant of this study was an English teacher in SMK NU 01 Hasyim Asy’ari Tarub in the academic year of 2019/2020. In this study, I used questionnaire, interview, classroom observation, and document analysis as data collection methods. The result revealed that the teacher integrated Team Pair Solo and picture with another teaching technique namely lecturing technique, other language skills (speaking, reading, and listening) and also a game. The game was intended to build the students’ enthusiasm in learning. This study showed that there was one main difficulty faced by the English teacher namely students’ limited vocabulary. In conclusion, Team Pair Solo and picture were an interesting and helpful technique and media that helped English teacher in the teaching and learning process and it was somewhat easy to be implemented. The technique and media also helped students to be actively engaged in the classroom activity.